2003
DOI: 10.1159/000069497
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Interleukin-1 Receptor Antagonist Intron-2 Polymorphism in Ischemic Stroke

Abstract: Evidence of inflammatory phenomena associated with atherosclerotic plaques is extensive. Interleukin-1 (IL-1) is one of the key modulators of the inflammatory response, and its activity is critically regulated by its receptor antagonist (IL-1Ra). A variable number of tandem repeats (VNTR) in intron 2 of the human IL-1Ra shows a common polymorphism that has been related to different production of IL-1Ra and IL-1 proteins. In monocytes, the less common allele 2 has been associated with an increased production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Previous studies did not find any significant association between the IL-1β polymorphism (–511) and ischemic stroke [8, 9]. Although the IL-1β polymorphism seems not to be a risk factor for ischemic stroke in the general population, it could be associated with a particular stroke subtype.…”
Section: Introductionmentioning
confidence: 77%
“…Previous studies did not find any significant association between the IL-1β polymorphism (–511) and ischemic stroke [8, 9]. Although the IL-1β polymorphism seems not to be a risk factor for ischemic stroke in the general population, it could be associated with a particular stroke subtype.…”
Section: Introductionmentioning
confidence: 77%
“…29 Furthermore, studies of the IL-1 and IL-1RA genes suggest that polymorphisms in both IL-1a and IL-1RA genes may be associated with increased risk of stroke. [30][31][32] Similarly, TNF-a has been hypothesized to play an important role in neurodegeneration. 33 TNF-a release from blood cells and serum levels of TNF-a were found to be elevated during the acute phase following stroke compared with healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…25 Our results contrast with those reported in an earlier Italian study that found a higher frequency of both carriage of the IL1RN*1 allele and homozygosity for IL1RN*1 among stroke survivors than in a control group. 26 However, the impact of survival bias must be considered. IL1RN*2 is associated with increased susceptibility to cerebral ischemia, 23 which may impact stroke severity and survival.…”
Section: Discussionmentioning
confidence: 99%